Eksplorasi, isolasi dan identifikasi Jamur entomopatogen yang menginfeksi serangga hama - Arsi Arsi; Yulia Pujiastuti; Suparman Surya Hadi Kusuma; Bambang Gunawan (Department of Plant Protection, Faculty of Agriculture, Universitas Jember - Indonesia, 2020)
ABSTRACT Entomopathogenic fungi are classified as a fungus that infects insect pests. Hyphae color that comes out of the insect's body depends on the type of entomopathogenic fungus that attacks it. The purpose of this research is to explore, isolate and identify entomopathogenic fungi that attack insect pests. Samples of dead insects were taken from vegetable crops in the highlands of Pagaralam City and the lowlands of Ogan Komering Ilir Regency. In addition, exploration is also carried out using insect bait methods. This method is carried out on soils taken from the highlands of the fencealam area and Pekanbaru area. Based on the results of entomopathogenic expolation in vegetable plants that infect insects in the field there are 2 types of fungi that attack the insect. Two types of entomapatogenic fungi were found to have characteristics, namely the first hyphal color is rather green which covers the entire body of the insect and the second is white hyphae. The fungus that attacks the insect, then isolated to the GYA media found two entomopathogenic fungi namely, Metarhizium sp. and Beauveria bassiana. Meanwhile, through insect bait using soil T. molitor larvae, one species of entomopathogenic fungus was found, namely Metarhizium sp. The most infected T. molitor larvae in the soil of origin of Pekanbaru in the 2nd and 4th weeks, namely, 21.90 and 29.33 tails. . Keywords: Entomopathogenic Fungus, Insect Pest and Tenibrio molitor